The New Phenomenon of Lithium Electrochemical (De)Intercalation in Mineral Clay Materials and Their Potential Application in Rechargeable Batteries - Shi-Jie Wen; Xiao-Tian Yin; L. Nazar (Active and Passive Electronic Components)
A new phenomenon of Li electrochemical (de)intercalation on the pure mineral clay materials has been evidenced for the first time. These tests are initialized by the idea of putting an electronic conducting polymer or a multi-valent metal oxide in the layer of the clay to modify the electronic properties and also to modulate the charge and discharge potential of the clay during the Lithium electrochemical (de)intercalation processing. In this paper, as the beginning of our research, we will first show the results of Lithium electrochemical charge and discharge processes on pure clay materials.